2018
DOI: 10.3389/frobt.2018.00077
|View full text |Cite
|
Sign up to set email alerts
|

A User Study on Robot Skill Learning Without a Cost Function: Optimization of Dynamic Movement Primitives via Naive User Feedback

Abstract: Enabling users to teach their robots new tasks at home is a major challenge for research in personal robotics. This work presents a user study in which participants were asked to teach the robot Pepper a game of skill. The robot was equipped with a state-of-the-art skill learning method, based on dynamic movement primitives (DMPs). The only feedback participants could give was a discrete rating after each of Pepper's movement executions ("very good," "good," "average," "not so good," "not good at all"). We com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Therefore, we present a system that does not need a predefined cost function or feature representation, and can learn successful movement skills from non-expert users in a couple of minutes. In contrast to work done by Vollmer and Hemion [3], we have looked into the drawbacks of using absolute-scale feedback from users, which is influenced by a drift in evaluation and the requirement of anchoring to a reference point, by utilizing preference-based feedback from users.…”
Section: A Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we present a system that does not need a predefined cost function or feature representation, and can learn successful movement skills from non-expert users in a couple of minutes. In contrast to work done by Vollmer and Hemion [3], we have looked into the drawbacks of using absolute-scale feedback from users, which is influenced by a drift in evaluation and the requirement of anchoring to a reference point, by utilizing preference-based feedback from users.…”
Section: A Related Workmentioning
confidence: 99%
“…The goal of the game is to catch the ball with the cup through skillful movement. Kober and Peters [19] have demonstrated that the cup-and-ball movement can be learned by a robot arm using DMP-based optimization, and Vollmer and Hemion [3] have demonstrated that Pepper is capable of mastering the game with human absolute scale ratings as reward. In this study, the cup-and-ball toy was built such that the size of the cup and ball resulted in a level of difficulty suitable for our purposes.…”
Section: Study 1: Human Feedbackmentioning
confidence: 99%
See 3 more Smart Citations